Race Differences in the Association Between Binge Drinking and Treatment Among First-Time Justice-System-Impacted Youth. (23rd September 2022) - Kan, Emily; Riano, Nicholas; Beardslee, Jordan; Frick, Paul; Steinberg, Laurence; Cauffman, Elizabeth
Abstract: Aims: We aim to determine whether there are racial/ethnic differences in the association between binge drinking frequency and community-based alcohol treatment among justice-system-impacted adolescents and young adults. Methods: We examined whether race/ethnicity moderated the relation between binge drinking and youths' likelihood of receiving alcohol treatment. The sample included 1216 male, first-time-arrested youth from the Crossroads Study (2011–2018). Participants were recruited from CA, PA and LA. Results: Among youth who binge drank occasionally, Black youth were less likely to receive alcohol treatment than White ( b = −0.08, 95% confidence interval [CI] [−0.13, −0.04]) and Hispanic/Latino ( b = −0.06, 95% CI [−0.09, −0.02]) youth. There were no differences between the White and Hispanic/Latino youth. Black youth who were frequent binge drinkers were as likely to receive alcohol treatment as White youth who binge drank significantly less often. There were no racial/ethnic differences in alcohol treatment at the highest level of binge drinking. Conclusion: Black youth who binge drink occasionally are less likely than White youth to receive alcohol treatment. The present findings highlight a need for efforts to mitigate racial disparities in access to or motivations to seek community-based treatment.